(untitled) (Fiep Bulletin - online, 2016)
The study aims to know the definitions of basic philosophical concepts that have coaches educators to approach the axiological structure their teaching. As posed the following research question: How do you define future educators coaches the basic philosophical concepts? A qualitative descriptive study was conducted, based on the phenomenology of the philosophical constructs. 20 teachers working in the Bachelor of Athletic Training Universidad Estatal de Sonora, applying a questionnaire that included three open questions were selected: What is success?, What is happiness? and what is good? The questionnaire was applied during the month of April 2014 For the content analysis of the collected data was taken as reference internal locus of control and external locus of control in the three concepts and values ??proposed by Wooden on "the pyramid of success". It was found that men have an external locus of control to describe the concepts success, happiness and well. In contrast, women had an internal locus of control to describe the same concepts. A close relationship between the concept of educators and coaches proposed by Wooden values ??was confirmed. The result is very similar although not teachers develop curricular success model proposed by Wooden, directing pedagogy to a model of desirable future success coaches.